Neoadjuvant Therapy in Pancreatic Cancer: Review Article - Pross, Moritz; Wellner, Ulrich F; Honselmann, Kim C; Jung, Carlo; Deichmann, Steffen; Keck, Tobias; Bausch, Dirk (JOP. Journal of the Pancreas, 2015)
Context Pancreatic cancer is still associated with a high mortality and morbidity for affected patients. To this date the role of neoadjuvant therapy in the standard treatment of pancreatic cancer remains elusive. The aim of our study was to review the latest results and current approaches in neoadjuvant therapy of pancreatic cancer. Methods We performed a literature review for neoadjuvant therapy in pancreatic cancer. We divided the results into resectable disease and local advanced pancreatic cancer. Results Neoadjuvant therapy in pancreatic cancer is safe. But currently no standard guidelines exist in neoadjuvant approaches on pancreatic cancer. For local advanced pancreatic cancer the available data tends to show a positive effect on survival rates for neoadjuvant approaches. Conclusion For resectable disease we found no benefit of neoadjuvant therapy. The negative or positive effects of neoadjuvant treatment in pancreatic cancer remain unclear for the lack of sufficient and prospective data. Image: University of Luebeck logo. Luebeck, Germany.